KETERLIBATAN PEREMPUAN MENCARI NAFKAH KELUARGA DALAM AL-QUR'AN - Norcahyono Norcahyono (Pascasarjana UIN ANTASARI Banjarmasin, 2015)
This research is motivated by the different opinions among Islamic thinkers about the womens involment in making a living for the family. In this research, the author attempts to reveal the thoughts of Quraish Shihab in Tafsir Al-Mishbah on the verses used as the argument of Islamic thinkers on whether or not women are allowed to earn a living for the family . The method used is analytical description with hermeneutical interpretation approach. This research found that according to the Quraish Shihab, the responsibility for the fulfillment of living in a family charged to men for several reasons, but women were allowed to engage in it for several conditions.